Blasted ORE Fragmentation And Its Influence On Excavators Productivity - Asri, Muhammad Anas (Universiti Sains Malaysia, 2018)
In order to achieve expectation global community from mining and quarrying industry, rock and ore blasting performance are crucial to improve the productions. One of the important key features to increase production of metals and minerals, the fragments produced after blasting must ideal so that it will follow according to the demands supplier and able to feed to crushing operation, if comminution needed. In order to assess the blasted ore fragmentation, numerical simulation method used by using image analysis. The software used is Split-Desktop, a software created by Split Engineering, used to determine fragments size and particle size distribution. Since fragmentation has effect on excavator’s productivity, excavator’s cycle time are taken on-site and recorded manually. Since ore will be feed to crusher on the site is limited to 400mm, that size become indicator for accepted fragments sizes .Based on the result obtained, the fragments produced at 400 mm are 65 % which considered above average, as only 65 % of total volume will send to crushing plant for recovery process. For excavators’ productivity, it causes 12.95 minutes later than planned.